Planet earth - Andorfer, Gregory; Kane, Georgann (Norwalk, Conn. : Easton Press Video, 1989)
Scientists explain current theories about the formation of the earth's continents, oceans and climate, and examine the earth's relationship to the sun and other planets.
Title from container
APD 601314
Music, Jack Tillar; photography, Norris Brock.
Richard Kiley, narrator.
Keywords: Earth sciences; Geology; Sun